Investigation on characterization of Ereen coal deposit - Jargalmaa, S.; Purevsuren, B.; Davaajav, Ya.; Avid, B.; Bat-Ulzii, B.; Ochirhuyag, B. (Mongolian Journal of Chemistry, 2016)
The Ereen coal deposit is located 360 km west from Ulaanbaatar and 95 km from Bulgan town. The coal reserve of this deposit is approximately 345.2 million tons. The Ereen coal is used directly for the Erdenet power plant for producing of electricity and heat. The utilization of this coal for gas and liquid product using gasification and pyrolysis is now being considered. The proximate and ultimate analysis show that the Ereen coal is low rank D mark hard coal, which corresponds to subbituminous coal. The SEM images of initial coal sample have compact solid pieces. The SEM image of carbonized and activated carbon samples are hard material with high developed macro porosity structure. The SEM images of hard residue after thermal dissolution in autoclave characterizes hard pieces with micro porous structure in comparison with activated carbon sample. The results of the thermal dissolution of Ereen coal in tetralin with constant weight ratio between coal and tetralin (1:1.8) at the 450ºC show that 38% of liquid product can be obtained by thermal decomposition of the COM (coal organic matter). Mongolian Journal of Chemistry 16 (42), 2015, 18-21